下列计算,正确的是 ( )
A. a 2 - a = a B. a 2 · a 3 = a 6 C. a 9 ÷ a 3 = a 3 D. ( a 3 ) 2 = a 6
下列运算正确的是 ( )
A. m · m = 2 m B. ( mn ) 3 = m n 3 C. ( m 2 ) 3 = m 6 D. m 6 ÷ m 2 = m 3
A. 3 x 2 - x 2 = 3 B. a · a 3 = a 3 C. a 6 ÷ a 3 = a 2 D. ( a 2 ) 3 = a 6
下列运算中,正确的是 ( )
A. x 2 + x 3 = x 6 B. x 3 + x 9 = x 27 C. ( x 2 ) 3 = x 6 D. x ÷ x 2 = x 3
下列计算正确的是 ( )
A. a 2 + a 3 = a 5 B. a 2 · a 3 = a 6 C. ( a 2 ) 3 = a 5 D. a 5 ÷ a 2 = a 3
下列计算中,结果是 a 6 的是 ( )
A. a 2 + a 4 B. a 2 ⋅ a 3 C. a 12 ÷ a 2 D. ( a 2 ) 3
A. 2 m 3 + 3 m 2 = 5 m 5 B. m 3 ÷ m 2 = m
C. m ⋅ ( m 2 ) 3 = m 6 D. ( m − n ) ( n − m ) = n 2 − m 2
A. a 12 ÷ a 3 = a 4 B. ( 3 a 2 ) 3 = 9 a 6
C. 2 a ⋅ 3 a = 6 a 2 D. ( a − b ) 2 = a 2 − ab + b 2
A. x 6 ÷ x 3 = x 2 B. ( − x 3 ) 2 = x 6 C. 4 x 3 + 3 x 3 = 7 x 6 D. ( x + y ) 2 = x 2 + y 2
A. x 2 · x 2 = x 6 B. x 4 + x 4 = 2 x 8
C. − 2 ( x 3 ) 2 = 4 x 6 D. x y 4 ÷ ( − xy ) = − y 3
A. 4 x ⋅ 2 x = 8 x B. 2 m + 3 m = 5 m
C. x 9 ÷ x 3 = x 3 D. ( − a 3 b 2 ) 2 = − a 6 b 4
下面计算正确的是 ( )
A. 3 a − 2 a = 1 B. 2 a 2 + 4 a 2 = 6 a 4
C. ( x 3 ) 2 = x 5 D. x 8 ÷ x 2 = x 6
A. x 7 ÷ x = x 7 B. ( − 3 x 2 ) 2 = − 9 x 4 C. x 3 · x 3 = 2 x 6 D. ( x 3 ) 2 = x 6
下列运算错误的是 ( )
A. ( m 2 ) 3 = m 6 B. a 10 ÷ a 9 = a C. x 3 · x 5 = x 8 D. a 4 + a 3 = a 7
A. 3 x + 4 y = 7 xy B. ( − a ) 3 · a 2 = a 5 C. ( x 3 y ) 5 = x 8 y 5 D. m 10 ÷ m 7 = m 3